MANAJEMEN STRATEGI SEKOLAH DALAM PROMOSI PENERIMAAN PESERTA DIDIK BARU DI SEKOLAH DASAR - Ria Sari; Nurhasanah; Erjati Abas; Subandi (STKIP Subang, 2023)
This study aims to describe the school's strategic management in the promotion of new student admissions in elementary schools. This research is a descriptive field research, which was conducted at SD Negeri 1 Sendang Agung, Bandar Mataram District, Central Lampung Regency, Lampung Province, in the odd semester of the 2023/2024 school year. Primary sources include interviews with the principal, teachers, staff and parents of students. Secondary data researchers get from books and articles and literature reviews related to the research title. Data collection techniques using interviews and literature studies. Data analysis techniques with data reduction, data presentation, and conclusions. Data validity test using source triangulation. The results of the study found that strategic management at SD Negeri 1 Sindang Agung school has been successful in designing and implementing new student admission promotion strategies, in identifying, facing, and overcoming challenges and obstacles in new student admission promotion efforts, this conclusion provides guidance for schools to improve the effectiveness of new student admission promotion and achieve their strategic goals, and that school strategic management at SD Negeri 1 Sendang Agung has succeeded in creating a positive impact on school reputation through new student admission promotion strategies.